TRADISI BARONGSAI DALAM MASYARAKAT TIONGHOA KEC.BANGKO KOTA BAGANSIAPIAPI - Rio Antoni; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is based on the shift of lion dance tradition in bagansiapi-api city. Problem formulation in this research are: (1) "How is the social system of lion dance tradition in Chinese society of town of fire?" (2) "How is the shift in lion dance tradition in the city of fire-fire?". This research aims to Know Social system in Chinese tradition, This research is done at Buddhasakyamuni Buddhist temple and Buddhasasana in june 2017. This research is qualitative research which become population in this research is young character of Chinese and Chinese society figure. the sample in this study was taken based on interview technique. Where the place taken into the sample is where the lion barongsai training in the monastery and interviewed him with questions that have been prepared in accordance with the formulation of the problems that have been determined. based on the results of research indicates that there is a variety of knowledge about beliefs that have different opinions about history, previous beliefs and get a response about the shift that occurred in lion dance. thus the hypothesis that there is a social system within the barongsai is very influential for each other so that a shift can occur in the city temple bagapiapiapi.Keyword : Barongsai tradition in the life of Chinese society